Makna Tradisi Peusijeuk dan Peranannya dalam Pola Komunikasi Lintas Budaya Masyarakat di Kota Langsa - Joko Hariadi; Muhammad Arif Fadhillah; Azrul Rizki (Universitas Medan Area, 2020)
The purpose of this research is to understand the meaning of the peusijeuk tradition in heterogeneous societies and its current position, especially in Langsa City. This study will be carried out as a qualitative study with a descriptive type of study. The use of qualitative descriptive methods is considered appropriate in this study, because it reveals the ongoing situation. Through field research, it was found that the peusijuek tradition is one of the Acehnese cultures which is still maintained by the people in Aceh, in that tradition contains Islamic religious values. This can be seen from the point of view that Islam has a universal concept that is able to unite and merge into various civilizations and cultures. For people in Aceh, the peusijuek tradition has a very philosophical meaning and purpose, namely to ask for and obtain safety, peace, and happiness in life. The conclusions in this study are: For people in Aceh, especially Langsa City, the peusijuek tradition has a very philosophical meaning and purpose, namely to ask for and obtain safety, peace, and happiness in life.